2017
DOI: 10.3389/fmicb.2017.02038
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus sp. Acting as Dual Role for Corrosion Induction and Corrosion Inhibition with Carbon Steel (CS)

Abstract: Present work investigated the role of five different bacteria species as a corrosion inducer as well as corrosion inhibitor with carbon steel (CS). We observed the ability of different bacteria species on the metal surface attachment, biofilm formation, and determined Peroxidase, Catalase enzyme activity in the detached biofilm from the CS surface. We found that each strain has diverse conduct for surface attachment like DS1 3.3, DS2 2.5, DS3 4.3, DS4 4.0, and DS5 4.71 log cfu/cm2 and for biofilm 8.3 log cfu/c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…Thus, protein and/or polysaccharide produced by E. asburiae ENSD102, uncultured Vitreoscilla sp. ENSG301, and A. lwoffii ENSG302 in response to different concentrations of Cu, Zn, Pb, Ni, and Cr could sequester the toxic metal ions, giving to the bacteria the time required for adaptation thus driving to the physiological or metabolic changes necessary for eliminating the toxic effect of these metals, i.e., expression of enzymes and transporters for pumping out the metal or metal-binding proteins ( Letelier et al, 2010 ; Mindlin et al, 2016 ; Nocelli et al, 2016 ; Karn et al, 2017 ). Thus, these bacterial strains might be an attractive biotechnological tool for bioremediation of toxic heavy metals from wastewaters.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, protein and/or polysaccharide produced by E. asburiae ENSD102, uncultured Vitreoscilla sp. ENSG301, and A. lwoffii ENSG302 in response to different concentrations of Cu, Zn, Pb, Ni, and Cr could sequester the toxic metal ions, giving to the bacteria the time required for adaptation thus driving to the physiological or metabolic changes necessary for eliminating the toxic effect of these metals, i.e., expression of enzymes and transporters for pumping out the metal or metal-binding proteins ( Letelier et al, 2010 ; Mindlin et al, 2016 ; Nocelli et al, 2016 ; Karn et al, 2017 ). Thus, these bacterial strains might be an attractive biotechnological tool for bioremediation of toxic heavy metals from wastewaters.…”
Section: Discussionmentioning
confidence: 99%
“…MIC has become one of the main threats in the field of oil and gas industry, water treatment industry, and marine engineering, which brings huge economic losses and potential safety hazards (Li et al., 2017). For a long time, numerous research works have been focused on sulfate reducing bacteria (SRB), iron oxidizing bacteria (IOB), sulfur oxidizing bacteria (SOB), and other bacteria (Enning and Garrelfs, 2014; Huber et al., 2016; Liang et al., 2016; Liu et al., 2016; Xu et al., 2016, 2018; Jia et al., 2017; Karn et al., 2017; Dou et al., 2018; Liu and Cheng, 2018). For the ubiquitous microorganisms in the natural environment, such as SRB, their MIC mechanisms have been studied in-depth, and comprehensive corrosion mechanisms have been well established (Venzlaff et al., 2013; Rajala et al., 2015; Li et al., 2018; Jia et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The biofilms detached from the coupons were assayed for peroxidase activity. The highest peroxidase were observed from DS4 (± 36U/ml) and the least from DS3 (±19.54 U/ml) with biofilms and almost no peroxidase in the control samples [55] . It was found that peroxidase and catalase were involved in the corrosion and the bacterial strains with the most MIC also produced the highest concentration of these enzymes.…”
Section: Recent Discoveries Of Peroxidase Isoforms From Different Soumentioning
confidence: 89%
“…Microbially influenced corrosion (MIC) is a physical, chemical and microbiological process in which corrosion and electrochemical processes are initiated, facilitated or accelerated by the dynamic support of microorganisms [55] . Microbes derive their energy by oxidizing and reducing a variety of chemical compounds, and they can change their metabolic activities and release various proteins based on the present conditions, of which in some cases lead to MIC.…”
Section: Recent Discoveries Of Peroxidase Isoforms From Different Soumentioning
confidence: 99%
See 1 more Smart Citation